2001
DOI: 10.1002/tox.10003
|View full text |Cite
|
Sign up to set email alerts
|

The toxicities of a polyunsaturated fatty acid and a microcystin to Daphnia magna

Abstract: Polyunsaturated fatty acids (PUFAs) are essential components of zooplankton diets. However, studies with PUFAs from cyanobacteria indicate toxic properties. We investigated the toxicity of the PUFA gamma-linolenic acid and the cyanobacterial peptide toxin microcystin-LR to Daphnia. The PUFA was acutely toxic at a concentration of 9 micrograms ml-1. The effect of microcystin-LR was not statistically significant at the concentration used (3 micrograms ml-1), but an additive effect with the PUFA was observed. Rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0
1

Year Published

2003
2003
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 19 publications
(16 reference statements)
0
23
0
1
Order By: Relevance
“…It is possible the liposomes used in our study may improve the digestibility of PUFAs in the daphnid gut (Ozkizilcik and Chu 1994) and/or provide oxidative stability to the PUFA supplements (McEvoy et al 1995;Nara et al 1998;Reinikainen et al 2001). Aquaculture studies have shown that the utility and bioavailability of dietary lipid amendments can be strongly affected by not only the type of lipid but also by the specific form or medium in which the lipid is delivered in the diet (Coutteau and Sorgeloos 1997).…”
Section: Discussionmentioning
confidence: 98%
“…It is possible the liposomes used in our study may improve the digestibility of PUFAs in the daphnid gut (Ozkizilcik and Chu 1994) and/or provide oxidative stability to the PUFA supplements (McEvoy et al 1995;Nara et al 1998;Reinikainen et al 2001). Aquaculture studies have shown that the utility and bioavailability of dietary lipid amendments can be strongly affected by not only the type of lipid but also by the specific form or medium in which the lipid is delivered in the diet (Coutteau and Sorgeloos 1997).…”
Section: Discussionmentioning
confidence: 98%
“…These pools may work synergistically with each other and potentially to other compounds. Linoleic acid was found to work synergistically with microcystin-LR when used against Daphnia (Reinikainen et al, 2001). These assays also demonstrated that linoleic acid was acutely toxic in concentrations of 9 µl/ml.…”
Section: Potential Roles Of Unsaturated Fatty Acids In Cyanobacteriamentioning
confidence: 73%
“…Harada et al (2000) correlated this activity with that observed on mosquito larvae. Unsaturated fatty acids were found to have toxicity comparable to microcystin on Daphnia magna (Reinikainen et al, 2001). Cumulatively, these studies suggest the potential for arthrocidal effects of unsaturated fatty acids.…”
Section: Introductionmentioning
confidence: 75%
See 1 more Smart Citation
“…There are direct tests of the effects of morphology (Ferrão-Filho and Azevedo 2003) and nutrition (DeMott and Mü ller-Navarra 1997; von Elert and Wolffrom 2001) on zooplankton feeding, but no study has unambiguously assessed how consuming cyanobacterial secondary metabolites affects zooplankton fitness. Past experiments have compared zooplankton performance when (1) immersed in media containing dissolved cyanotoxins (Reinikainen et al 2001) or cyanobacterial extracts (Wheeler et al 1942), (2) fed diets containing cyanobacteria versus being starved (Arnold 1971; reviewed by Wilson et al 2006a), (3) fed diets containing cyanobacteria versus foods supporting better growth (Arnold 1971; reviewed by Wilson et al 2006a), (4) fed diets of two conspecific cyanobacteria that are or are not toxigenic to mammals (Smith and Gilbert 1995), and (5) fed diets consisting of a wild-type cyanobacterium containing microcystins or its mutant that lacks the ability to produce microcystins but may produce other toxic, nonmicrocystin oligopeptides (Rohrlack et al 2005).…”
mentioning
confidence: 99%